(untitled) (FULafia Journal of Science and Technology, 2019)
The study focuses on the analysis of 33kv distribution feeder network in Ibadan Electricity Company, Ota. The main aim of this research is to estimate the reliability of 33-KV feeders which are secondary distribution network of the system. The study determines the Failure Rate, the Mean Time between Failures (MTBF), Mean Time to Failure (MTTF), Availability and reliability of the network. This study uses statistical analytical method. Statistical analytical methods provide useful and higher accuracy of result since it provides high tolerance to uncertainties. The result shows that the mean reliability of the supply system was 74.41%, and thus for a developing nations like ours, the reliability is partly satisfactory.